Proteomic Analysis of Heart and Kidney Tissues in Healthy and Metabolic Syndrome Rats after Hesperidin Supplementation. Issue 10 (4th May 2020) - Pla‐Pagà, Laura; Guirro, Maria; Gual‐Grau, Andreu; Gibert‐Ramos, Albert; Foguet‐Romero, Elisabet; Catalán, Úrsula; Mayneris‐Perxachs, Jordi; Canela, Nuria; Valls, Rosa M.; Arola, Lluís; Solà, Rosa; Pedret, Anna
Abstract : Scope: Proteomics has provided new strategies to elucidate the mechanistic action of hesperidin, a flavonoid present in citrus fruits. Thus, the aim of the present study is to determine the effects of hesperidin supplementation (HS) on the proteomic profiles of heart and kidney tissue samples from healthy and metabolic syndrome (MS) rats. Methods and results: 24 Sprague Dawley rats are randomized into four groups: healthy rats fed with a standard diet without HS, healthy rats administered with HS (100 mg kg −1 day −1 ), MS rats without HS, and MS rats administered with HS (100 mg kg −1 day −1 ) for eight weeks. Heart and kidney samples are obtained, and proteomic analysis is performed by mass spectrometry. Multivariate, univariate, and ingenuity pathways analyses are performed. Comparative and semiquantitative proteomic analyses of heart and kidney tissues reveal differential protein expression between MS rats with and without HS. The top diseases and functions implicated are related to the cardiovascular system, free radical scavenging, lipid metabolism, glucose metabolism, and renal and urological diseases. Conclusion: This study is the first to demonstrate the protective capacity of hesperidin to change to the proteomic profiles in relation to different cardiovascular risk biomarkers in the heart and kidney tissues of MS rats. Abstract : The effect of hesperidin supplementation on the proteomic profile of heart and kidney tissue samples of healthy and metabolic syndrome rats is determined. This work is the first study that demonstrate the protective capacity of hesperidin to change the proteome profile of metabolic‐syndrome rats.